In –service training in the innovative use of ICT. An action-research in Pre–school and Primary Education - Fernández-Díaz, Elia; Calvo Salvador, Adelina (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
We describe a research study aimed at consolidating a collaborative working that promotes the use of ICT to bring about a change in the approach to teaching in schools. Via an action research carried out from 2006-2010 in Pre-school and Primary Education, and in a blended–learning environment, we were able to set up collaborative projects such as digital child sponsoring or tutoring between pupils, as well as different professional development strategies such as scaffolding between teachers or the training for research. The work enabled us to develop innovation in education processes. The results permitted us to highlight the importance of creating communities of practice in which the meaning of the school 2.0 is reconsidered and discussed in a social learning environment.